Luckiest girl alive - Knoll, Jessica (New York : Simon & Schuster, 2015)
This debut novel follows a young woman striving to create the perfect life--husband, home, career--until a violent incident from her past threatens to unravel everything and expose her most shocking secret of all.
"A novel"--Jacket.
Keywords: Young women -- Fiction; Women journalists -- Fiction; Life change events -- Fiction; Secrecy -- Fiction; New York (N.Y.) -- Fiction